Papillary lung adenocarcinoma with psammomatous calcifications. (2018) - Gupta, Ankit; Palkar, Atul; Narwal, Priya
Abstract: We present the case of a 71 y/o man with chronic obstructive pulmonary disease (COPD) who presented with 3 weeks of cough, phlegm, fever, and failed outpatient antibiotic therapy for pneumonia. CT of the chest showed unilateral interstitial changes and bronchoscopic biopsies demonstrated primary lung papillary adenocarcinoma and extensive concentric psammomatous calcifications.